Evidence of the Middle-Income Trap in Latin American Countries: Factor Analysis Approach Using Regression and the ARDL Model - Galvan, Lisette Paola Cervantes; Campo, Carlos Carmona; Stanojevic, Savo; Alzate, David Villada (Frontiers in Environmental Science, 2022)
The middle-income trap (MIT) is often accompanied by the decline or stagnation of economic growth, unreasonable domestic industrial structure, and serious polarization between the rich and the poor. However, due to different international environments, different specific national conditions, and different development policies adopted by each country, how to get out of the MIT varies. This study carries out an analysis of different economic growth factors of Latin American countries (we selected 19 MIT countries out of 33) and compared them with Singapore and Korea, which are in a high-income range. We used a regression model to find the relationship of variables in each country and the impact on the economic growth due to these variables. The study finds using correlation and regression analysis, that trade and foreign direct investment (FDI) play a major role in avoiding the MIT by having a strong regression (R2 = 1.481*** for S. Korea, R2 = 0.65 for Singapore) with the gross domestic product (GDP) for high-income countries while having a weak regression in Latin American countries. Another factor is that industrialization and services export play a vital role in avoiding the MIT in Singapore and South Korea, and the same model should be used in Latin American countries to avoid the MIT. Furthermore, using the panel ARDL model we validated the results of a regression model and established that similar factors are impacting Latin American countries’ MIT. Correlation analysis is used to determine the relationship of selected factors and their impacting strength on the growth of an economy. In the final section, we present Latin American countries, and their main policy gaps according to their unique characteristics and recommend a policy with suggestions for avoiding the MIT by comparing their economies with those of high-income countries.